Life Satisfaction After Burn Injury—A Comprehensive Review - Maria Fernanda Hutter; Christian Smolle; Julia Kleinhapl; Lars-Peter Kamolz (European Burn Journal)
Burn injuries can have long-lasting effects not only on a person’s bodily integrity but also on their psychosocial well-being. Since medical advancements have increased survival from burn injuries, improving psychosocial health has become a pivotal goal for burn rehabilitation. Besides health-related quality of life, life satisfaction has become an important parameter for evaluating long-term outcomes after burns. We reviewed life satisfaction after burns among adult burn patients to evaluate the current assessment methods and gain insight into recovery patterns. PubMed, EMBASE, Medline, and Cochrane Library were searched systematically for studies in the English language covering life satisfaction after burns, resulting in the inclusion of 18 studies. The Satisfaction With Life Scale (SWLS) was the most commonly used assessment tool. Others included the Life Satisfaction Index-A (LSI-A) and a non-standardized tool. Most studies’ recovery patterns showed a decreased life satisfaction post-burn injury. There was strong agreement that inhalation injury, body dysfunction, an extended hospital stay, and psychological illness before the injury are possible determinants of post-burn life satisfaction and have shown a negative correlation. There seems to be a consistent use of assessment tools, which opens up the possibility of a further comparative investigation to better understand factors that influence life satisfaction after a burn so that this knowledge can be used to improve patients’ recovery.